Analisis Faktor-Faktor Yang Memengaruhi Keluhan Kesehatan Di Indonesia Menggunakan Metode Regresi Data Panel - Rahmayuni, Titin; AR, Fitriana; Salwa, Nany; Nurhasanah, Nurhasanah (Syiah Kuala University, 2024)
Health complaints are one aspect of the problem that is the focus of attention in Indonesia. Over the past 3 years, the percentage of health complaints in Indonesia has increased. One of the ways that can be done to reduce the problem of health complaints is to find out the factors that influence it. This study aims to find a suitable model to determine the factors that influence health complaints in Indonesia. To find out the factors that influence health complaints in Indonesia, this study uses a panel data regression analysis method with 3 basic models, namely the Common Effect Model (CEM), Fixed Effect Model (FEM), Random Effect Model (REM). The data in this study consists of cross section data in the form of 34 provinces in Indonesia and time series data in the form of data from 2020 to 2022 with 1 dependent variable and 9 independent variables. The results showed that the selected model of health complaints in Indonesia was the Random Effect Model with individual effects. This model produces an R2 value of 58.19% and an adjusted R2 value of 54.09%. This study obtained 3 significant variables, namely the sick population who did not seek treatment, the population who self-medicated, and the birth process that was not assisted by health workers. Meanwhile, the variables that have a positive effect are the sick population that does not seek treatment, women with marital status using family planning, and population who smoke.